Towards a territorial equity through the criterion-based assessment of socio-economic inequalities. Case of the Province of Boumerdes - Bouchama, Ouahiba; Alouat, Mohamed; Berberi, Rania; Derouiche, Amina (Technium Social Sciences Journal, 2022)
In spatial planning, inequalities represent imbalances and disparities in the distribution of income, equipment and development opportunities. For such reason, it is necessary to apprehend, analyze and deal with these disparities, in order to attain the objectives, including the coherent development of the territories. As a fact of matter, the forms of inequalities in Algeria have been the subject of the national policy of planning and sustainable development which were motivated by the implementation of various tools and plans of development at the national, regional and provincial level, namely the National Scheme of Territorial Development (SNAT), the Regional Scheme of Territorial Development (SRAT) and the Plan of Territorial Development of the Province (PATW). Indeed, our study consists of measuring the disparities by adopting economic and housing criteria in the province of Boumerdes, and defining, as consequence thereof, the classification of its whole municipalities in order to be able to reduce the inequalities and to seek other horizons of development in the marginalized zones.